2003
DOI: 10.1177/0193945903252419
|View full text |Cite
|
Sign up to set email alerts
|

Reworking Professional Nursing Identity

Abstract: In spite of professional socialization through nursing education programs, new graduates experience stress as they become working professionals. This grounded theory study explores experienced nurses' perceptions of how they became professional. The central problem for nurses was dissonance between expectations and experiences; they addressed this through an iterative, three-stage process of reworking professional identity. The stages of this process are assuming adequacy, realizing practice, and developing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 16 publications
0
116
0
2
Order By: Relevance
“…I have grounded my argument in the theory that professional identity is based on self-assessment in the work environment [MacIntosh 2003;Öhlén and Segesten 1998] and is shaped by the rules of conduct in place for that environment, or governmentality. I have demonstrated that protocols are tools instituted by the governing body and internalised by nurses to assess their quality of work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…I have grounded my argument in the theory that professional identity is based on self-assessment in the work environment [MacIntosh 2003;Öhlén and Segesten 1998] and is shaped by the rules of conduct in place for that environment, or governmentality. I have demonstrated that protocols are tools instituted by the governing body and internalised by nurses to assess their quality of work.…”
Section: Resultsmentioning
confidence: 99%
“…A nurse's self-evaluation of competence within the work environment is a key component in professional identity and consequently self-worth [James 1890;MacIntosh 2003;Öhlén and Segesten 1998]. This article demonstrates that practices associated with self-evaluation and professional identity may come into confl ict when a nurse's 'rules for conduct of the self' do not match the professional environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] In addition to practical and theoretical skills, it is necessary that the student and the professional nurse are socialized into a professional culture in order to cope with the profession and develop professional competence. [46] The purpose of the clinical placement is to enable nursing students to add professional competence to their knowledge base by integrating theory with practice and vice-versa. There are many challenges for nursing students in the different learning situations experienced during their clinical placement.…”
Section: Relevance Of Wil-pm For Nursing Students In Clinical Placementmentioning
confidence: 99%
“…Certains participants peuvent ressentir une certaine redevance ou dépendance envers l'infirmière et ainsi accepter de participer à l'étude sans réellement le vouloir (Head et Ritchie, 2004 (MacIntosh, 2003).…”
Section: « êTre Avec L'autre »unclassified